PEMBERIAN MOTIVASI BELAJAR BAHASA INGGRIS METODE DUBBING DAN SUBTITLING PADA MAHASISWA STIKES YARSI MATARAM - Aristiawan, Danul (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
As a solution to motivating students to learn and communicate with English is by providing attractive teaching media and effective learning methods. One of the interesting teaching media is the use of film media. In the film, an interesting story is presented in the form of illustrated animation and is equipped with an audio voice so that it can engage students to be interested in learning English. In addition, effective learning methods can also help students understand the information being taught. One of the learning methods that can be applied to motivate students to communicate in English is by using dubbing and subtitling methods. Dubbing is a method of imitating the voice of an actor who plays a role in a film. This can make students interested in communicating in English because they are playing a film dialogue scene played by the actor in the film. Meanwhile, subtitling is a method of transcribing film dialogue that is usually displayed at the bottom of the screen. In other words, teaching media and learning methods are two important things that cannot be separated and support each other as a means for students to understand the information provided. Effective and efficient media and methods can help students engage in learning English and at the same time be motivated to communicate in English